2017
DOI: 10.1021/acssuschemeng.7b00178
|View full text |Cite
|
Sign up to set email alerts
|

Using Ionic Liquids To Tune the Performance of Aqueous Biphasic Systems Based on Pluronic L-35 for the Purification of Naringin and Rutin

Abstract: Aqueous biphasic systems (ABS) based on Pluronic L-35, a (EO) x -(PO) y -(EO) x triblock copolymer, were determined and applied in the separation of two structurally similar flavonoids (naringin and rutin). Two sets of phase formers were paired with Pluronic L-35, one comprising conventional salts/buffer and other including cholinium-based ionic liquids (ILs). It is shown that while the conventional salts induce an unbalanced and strong salting out leading to complete extraction of flavonoids to the same phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 53 publications
4
19
0
Order By: Relevance
“…The ability of the studied cholinium‐based compounds to form ABS can be ranked as follows: [Ch][DHP] > [Ch][DHC] > [Ch][Ac] > [Ch][Bic] > [Ch]Cl. The tendency observed is in agreement with previous reports for ABS composed of [Ch]X and Pluronic L‐35 …”
Section: Resultssupporting
confidence: 93%
“…The ability of the studied cholinium‐based compounds to form ABS can be ranked as follows: [Ch][DHP] > [Ch][DHC] > [Ch][Ac] > [Ch][Bic] > [Ch]Cl. The tendency observed is in agreement with previous reports for ABS composed of [Ch]X and Pluronic L‐35 …”
Section: Resultssupporting
confidence: 93%
“…[Ch]Cl and [Ch][Ac] ions compete for water molecules around PEO chains of amphiphilic copolymers, increasing the micelle-micelle interactions and decreasing the T CP (enlargement of the two-phase region) [5,8]. Our results are in agreement with findings of Teixeira-Pinto et al [16], that observed a reduction of T CP in C 10 E 4 nonionic surfactant aqueous solutions + salts (SO…”
Section: Pluronic F68 + Ils Atpms Phase Diagramssupporting
confidence: 91%
“…The presence of ions affected not only ATPMS equilibria but also the solutes' partition, i.e. electrolyte solutions can affect their solubility in the coexisting phases [6,8,45]. It is evident that with the addition of more hydrophobic ILs (…”
Section: Partition Of Pure Commercial Ccm Using Pluronic F68 + Ils Atpmsmentioning
confidence: 99%
See 2 more Smart Citations